Efficacy and safety of third-line treatment with anlotinib in patients with refractory advanced non-small-cell lung cancer (ALTER-0303): a randomised, double-blind, placebo-controlled phase 3 study. (September 2017) - Han, Baohui; Li, Kai; Wang, Qiming; Zhao, Yizhuo; Zhang, Li; Shi, Jianhua; Wang, Zhehai; Cheng, Yin; He, Jianxing; Shi, Yuankai; Chen, Weiqiang; Wang, Xiuwen; et al.
Abstract: Background: Anlotinib hydrochloride, an oral tyrosine kinase inhibitor targeting VEGFR, FGFR, PDGFR, and c-kit, showed promising efficacy in a phase 2 study. Here, we evaluated the efficacy and safety of anlotinib as third-line treatment for advanced non-small-cell lung cancer. Methods: We did a randomised, double-blind, placebo-controlled phase 3 trial (ALTER-0303) at 31 sites. Eligible patients with stage 3B/4 non-small-cell lung cancer who progressed after at least two lines of previous therapies were randomly assigned (2:1) to receive anlotinib (12 mg once a day from day 1 to 14 of a 21-day cycle) or placebo until progression or intolerable toxicity. Enrolled patients harbouring EGFR or ALK mutations must have failed in previous match-targeted therapies. The primary endpoint was overall survival. This trial is registered with ClinicalTrials, numberNCT02388919 . Findings: Between February, 2015, and August, 2016, we randomly assigned 437 patients. The baseline characteristics of the anlotinib group (n=294) and placebo group (n=143) were well balanced in age, gender, ECOG performance status, and gene status. With 292 overall survival events (67%), a significant improvement in overall survival was observed in the anlotinib group compared with the placebo group (hazard ratio 0·68, 95% CI 0·54–0·87 p=0·0018), according to investigator-assessed results (table ). Interpretation: The ALTER-0303 trial met its primary endpoint; anlotinib significantly improved overall survival in advanced non-small-cell lung cancer with a manageable safety profile. The results strongly suggest that anlotinib should be considered as a candidate for the third-line treatment or beyond in advanced non-small-cell lung cancer. Funding: Chia-tai Tianqing Pharmaceutical Co Ltd.